Evaluation of the effectiveness of surgical treatment of patients with Mirizzi syndrome - Gaibullayev Temurbek Zakirovich; M.M. Akbarov; M.S. Nishanov; Usmonov A.A (Genius Journals, 2023)
Mirizzi's syndrome is a rare disease of the horse's excretory tract, and according to the literature, it is detected in 0.5-5% of patients suffering from various forms of equine stone disease
Keywords: Mirizzi syndrome; diagnosis; computed tomography; retrograde pancreatocholangiography